Interplaying Reading and Writing in ESL/EFL: A Literature Review of Strategies for Indonesian Teachers - Anaktototy, Karolis (Universitas Lancang Kuning, 2023)
The importance of integrating reading and writing activities in ESL/EFL classes cannot be overstated, especially in Indonesia where low literacy levels and reading interest present a challenge for teachers. This study conducted a literature review of 120 articles and books over the last 10 years taken from ZLibrary and Google Scholar's free database to identify effective strategies for incorporating reading and writing activities into the classroom that can be applied in many contexts and countries, including Indonesia. It was found that exposing students to various English text structures through these activities can greatly enhance their writing skills. By examining this literature, the study identifies 6 effective strategies for integrating reading and writing activities in ESL/EFL classes, namely summarizing, paraphrasing, short story writing, comparing and contrasting, discovery learning, and project-based learning. Teachers can employ these strategies to interplay reading and writing activities, helping students develop critical thinking skills, vocabulary, and writing abilities. In conclusion, it is clear that integrating reading and writing activities in ESL/EFL classes can provide a comprehensive approach to teaching and nurture students' writing skills, even in countries with low literacy levels and limited reading interest like Indonesia. Future research should explore additional effective strategies for integrating these activities.